2023
DOI: 10.3389/fpls.2023.1142856
|View full text |Cite
|
Sign up to set email alerts
|

High-quality genome assembly and genetic mapping reveal a gene regulating flesh color in watermelon (Citrullus lanatus)

Abstract: The unique color and type characteristics of watermelon fruits are regulated by many molecular mechanisms. However, it still needs to be combined with more abundant genetic data to fine-tune the positioning. We assembled genomes of two Korean inbred watermelon lines (cv. 242-1 and 159-1) with unique color and fruit-type characteristics and identified 23,921 and 24,451 protein-coding genes in the two genomes, respectively. To obtain more precise results for further study, we resequenced one individual of each p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…2. The non-synonymous SNP (A>G) in ClPSY1 was also detected by Nie et al [ 4 ]. In higher plants, RCCR is essential for chlorophyll degradation during leaf senescence and fruit ripening.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…2. The non-synonymous SNP (A>G) in ClPSY1 was also detected by Nie et al [ 4 ]. In higher plants, RCCR is essential for chlorophyll degradation during leaf senescence and fruit ripening.…”
Section: Discussionmentioning
confidence: 58%
“…Song et al [ 19 ] conducted a comparative analysis of the whole-genome sequence of 24 watermelon inbred lines (six orange-, nine red-, and nine yellow-fleshed) and reported that the non-synonymous SNP (A>G) in the first exon of ClPSY1 , which is the same SNP discovered in our study, exhibited an 87.5% matching rate to flesh color; the SNP (G) for orange color was present in all six orange-fleshed lines, two red-, and one yellow-fleshed lines. In addition, by performing a high-resolution genetic mapping of an F 2 population derived from red- and orange-β-fleshed inbreds, Nie et al [ 4 ] identified two carotenoid biosynthesis genes in the QTL intervals: ClPSY1 on Chr. 1 and RCCR encoding red chlorophyll catabolite reductase (RCCR) on Chr.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important species in relation to a high cultivation rate worldwide is watermelon (Citrullus lanatus). The referenced genome of 242-1 isolate was published in 2023 [88], where the authors utilised Oxford Nanopore MinION and Illumina HiSeq 2500 systems and described the genome size of 361.7 Mb with 22.0x data coverage and 23,921 proteincoding genes. Due to the existence of a huge number of watermelon varieties, the genome sequencing of other subspecies and species has also been attempted several times by other researchers.…”
Section: Cucurbits Genomes Complexity and Characterisationmentioning
confidence: 99%
“…Due to the existence of a huge number of watermelon varieties, the genome sequencing of other subspecies and species has also been attempted several times by other researchers. DNA sequences for the Korean cultivar 159-1 [88], as well as for Charleston Gray [89], a dessert watermelon cultivar, have also been obtained. Moreover, in 2013 the genome of C. lanatus subsp.…”
Section: Cucurbits Genomes Complexity and Characterisationmentioning
confidence: 99%